Axel Törneman: 1880-1925 - A Pioneer in Times of Change - Theorell, Anita 1941- (Bokförlaget Stolpe, 2021)
Axel Törneman (1880-1925) is one of the pioneers of modern Swedish art history. He is best known for his large frescos in the Stockholm City Hall and elsewhere. Nonetheless, few people today have heard of him. He pursued his own path, consciously choosing not to belong to any artistic group. That may also be a factor in his relative anonymity. This is the first biography of Törneman, written by Anita Theorell, who has a doctorate in art history. The book includes a large number of his lesser known easel paintings as well as previously unpublished material such as photos and drawings. Theorell presents an intense, bold, headstrong artist who lived far too short a life, one that was at times quite dramatic
Keywords: Törneman, Axel -- 1880-1925; Biografie; Bildband